ANALISIS PENGARUH KOORDINASI INTRA-ORGANIZATIONAL TERHADAP KINERJA PUSKESMAS DALAM PROGRAM PEMANTAUAN PERTUMBUHAN DAN PERKEMBANGAN BALITA (Studi di Puskesmas Kabupaten Banjar) - Ayu Riana Sari Azwari (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
Data of toddler with underweight in Puskesmas Banjar from 2011 to 2014 has increased. Thenational target for toddlers with underweight is <5% and the target area for toddlers withunderweight is <1.5%. In national target, the increase is still below the target of 3.25%. However,when compared with the target area, the percentage of children under five with underweight at thePuskesmas Kabupaten Banjar Martapura is still a problem. This study aims to analyze the influenceof intra-organizational coordination on the performance of Puskesmas in growth and developmentchildhood program. This research is a quantitative research with analytic observational approach.The sample of research is 18 Puskesmas. The number of respondents from this study amounted to 126people spread in 18 Puskesmas. So the information from each puskesmas obtained from 7respondents. The results of the study were analyzed based on the type of dependency theory ofThompson and coordination mechanisms theory of Mintzberg. The result of the research shows thatcoordination adjustment has an effect on performance. This means that if the type of dependence inaccordance with the coordination mechanism, it will have a positive impact on the resultingperformance. The results of this study prove the theory of coordination by Shortell, coordination is aconscious activity to unite and harmonize different potentials so that it can function harmoniously toachieve organizational goals. In this research, the coordination is operationalized to unify theactivities implemented by the involved sections in the Puskesmas to achieve the optimal performanceof growth and development childhood program.